2021
DOI: 10.1523/jneurosci.0793-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Manipulating Cone Responses to Naturalistic Inputs

Abstract: Primates explore their visual environment by making frequent saccades, discrete and ballistic eye movements that direct the fovea to specific regions of interest. Saccades produce large and rapid changes in input. The magnitude of these changes and the limited signaling range of visual neurons mean that effective encoding requires rapid adaptation. Here, we explore how macaque cone photoreceptors maintain sensitivity under these conditions. Adaptation makes cone responses to naturalistic stimuli highly nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 69 publications
3
49
0
Order By: Relevance
“…These properties are apparent in both the cone current ( Figure 6A , top) and voltage ( Figure 6A , bottom) responses. These properties of the cone responses are created by rapid adaptation in the phototransduction process ( Angueyra et al, 2022 ), due to a light-dependent increase in PDE activity ( Nikonov et al, 2000 ), which causes the gain of the cone light response to be modulated during each cycle of the sinusoid. The cone responses are well captured by an empirically derived biophysical model of cone phototransduction (see Figure 6—figure supplement 1 , Materials and methods and Angueyra et al, 2022 for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties are apparent in both the cone current ( Figure 6A , top) and voltage ( Figure 6A , bottom) responses. These properties of the cone responses are created by rapid adaptation in the phototransduction process ( Angueyra et al, 2022 ), due to a light-dependent increase in PDE activity ( Nikonov et al, 2000 ), which causes the gain of the cone light response to be modulated during each cycle of the sinusoid. The cone responses are well captured by an empirically derived biophysical model of cone phototransduction (see Figure 6—figure supplement 1 , Materials and methods and Angueyra et al, 2022 for details).…”
Section: Resultsmentioning
confidence: 99%
“…A front-end model of cone phototransduction was added to the model for the analyses in Figures 6 — 8 . This model consists of a set of differential equations that capture measured cone responses to a broad range of stimuli ( Angueyra et al, 2022 ; Figure 6—figure supplement 1 ). All parameters of the cone model were set by previous measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Decades of physiological studies, however, have observed that notable nonlinearities occur in both space and time. Temporally, photoreceptor responses are strongly shaped by adaptation and hence are poorly described by linear models ( 34 36 ). Spatially, bipolar cells rectify (a nonlinear process) the signals that provide inputs to RGCs ( 9 , 10 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we derived analytic results for dim-light responses in rods and cones that show how response sensitivity and dynamics change as the Ca 2+ kinetics is altered due to fast buffering and change in the extracellular Ca 2+ concentration. Our analytic formulas not only provide quantitative and conceptual insight, but they are also a means to easily compute photoreceptor responses based on underlying biophysical parameters without having to numerically solve a system of differential equations, which can be used as input to study downstream processes in the retina [59].…”
Section: Discussionmentioning
confidence: 99%